Considerações sobre a biologia de Haemulon steindachneri (Jordan & Gilbert, 1882)- Pisces, Osteichthyes - ocorrente na região da Central Nuclear Almirante Álvaro Alberto, em Angra dos Reis, RJ - Brum, Mário Jorge Ignácio (1983)
The data used in this work, are the result of the Project for the Analysis of the Fauna and Flora in the area of the Almirante Álvaro Alberto Nuclear Plant, in Angra dos Reis, completed before the plant had begun operation. The collection of specimens, showed the H. steindachneri as the most frequent fish species, therefore qualifying for testing as an indicator of environmental alterations, since it belongs to an ecosystem which is about to suffer the impact of a nuclear plant. Thus, the biology of this fish was studied in depth in the search for parameters that might permit the future detection of changes in its biology, resulting frorn the changes in environment. From the characteristics that were studied certain conclusions can be made: the male of the species is larger than the female; every year, the young individuals appear in Autumn, mature in Spring and spawn in Summer; and its capture in great quantities by bottom-trawl is due to the fact that this species lives in large schools close to the bottom, where it feeds on tbe invertebrates that live there.